Estudo do comportamento à compressão de estacas metálicas curtas em solo sedimentar - Gonçalves, Sergio Fernandes (2008)
The present work aims at analyzing the behavior of short metallic piles type profile "H", W 150 x 22,5, submitted to static load test to compression, executed in 3, 4 and 5m depths, in sedimentary ground at the Experimental Field of the Geotechnical Engineering of UFSM (CEEG/UFSM)., The under soil presents a superficial layer thickness of 5m at the research location, consisting of plastic clay-arenaceous, rigid consistency, followed by a sand layer with thickness varying from thin to average, very compact and up to 14 m. Correlations were made between the rupture loads of the essayed props and the parameters obtained through soundings of simple recognition (SPT), that is, estimated rupture loads by methods of calculation of consecrated load capacity. Extrapolation criteria were applied load x stress of the curves and calculation equations of maximum penetration, with the objective of creating rupture loads. Also information was obtained for the increment of a database, aiming at offering other execution options of foundations for the Santa Maria region. With the results, analyses of load transfers were performed, plus comparisons between the methods, in addition to the parameter definitions for the rupture load on metallic props, according to present objectives.